Cicho pójdę w nowe dni – cisza w poezji Stanisławy Plewińskiej - Joanna Rychter (Język. Religia. Tożsamość, 2023)
Plewińska drew creative inspiration from multi-sensory contact with nature in the countryside. For her, auditory perception was extremely important. In addition to sounds, however, the sensations resulting from their absence were equally significant. The state of silence is present in each of her poetry books. At the linguistic level, it is conveyed conventionally, i.e. using the noun „cisza” [silence], and its derivatives such as „cicho” [quietly], „cichutko” [very quietly], „cichy” [quiet], „cichnąć” [to fall silent], as well as „milczenie” [stillness] and „milczeć” [to be silent], and „zamilknąć” [to fall silent]. Similarly to folk tradition, the state of silence is used to celebrate transition (from life to death, from adulthood to old age) and to evoke the unknown and mysterious, i.e. the afterlife.